Research on the influence of system parameters on the electromechanical dynamics of a large wind turbine drivetrain - Shijie Zhang (Elsevier, 2021)
A wind turbine (WT) is a complex system integrating mechanical and electrical controls, and WTs can be coupled and interact with each other. This paper established an electromechanical model of a WT drivetrain and explored the influence of the system parameters of the WT drivetrain on the dynamic response and current harmonics. The results show that the introduction of a generator produces an electromagnetic frequency component in the mechanical system and that the mechanical parameters directly determine whether the generator undergoes periodic motion, quasiperiodic motion or chaotic motion, which affects the power generation efficiency of a WT. The research results can be used as a reference for the mechanical design of WT drivetrains and the selection of generators.